The population of Ctenomys from the Ñacuñán Biosphere Reserve (Mendoza, Argentina) belongs to Ctenomys mendocinus Philippi, 1869 (Rodentia, Ctenomyidae): molecular and karyotypic evidence - Parada, Andrés (2012)
Subterranean tuco-tucos of the genus Ctenomys are caviomorph rodents comprising a complex of over 50 nominal species found in the southern half of South America. The validity of several nominal forms awaits a proper assessment. The population of Ctenomys from Ñacuñán Biosphere Reserve (Mendoza, Argentina) has been classically considered to represent a distinct species and has been commonly referred as Ctenomys eremofilus. Based on molecular and cytogenetic analysis we assessed the taxonomic status of the Ctenomys population of Ñacuñán. Specimens analyzed showed two very similar chromosome complements (2n=48 and 2n=50), the latter being widely distributed in populations of C. mendocinus. Similarly, haplotypes recovered from Ñacuñán specimens are very similar and sister to those recovered from specimens of C. mendocinus. Considering this evidence we conclude that the individuals of Ctenomys from Ñacuñán population should be assignable to C. mendocinus.